Fractional-Order Delay Differential Equation with Separated Conditions: Piyachat Borisut, Chaiwat Auipa-arch - Team, Support (Thai Journal of Mathematics, 2021)
In this paper, In this paper, we study and consider the existence and uniqueness solution of functional delay differential equation and separated condition. The existance result via Schaefer’s fixed point theorem is considered. The existence and uniqueness result via Boyd and Wong fixed point theorem is presented.